Developing Bilingual Guidebook of ‘Southern Beaches’ of Malang - Nabilla Hilda Faahira Nata (Jurnal Linguistik Terapan, 2021)
This study discussed Developing a bilingual guidebook for Southern Beaches in Malang. This research used was the Design and Development Research method with the procedures of Analysis, Product Design, Product Development, Implementation, and Evaluation. According to the expert validator, there were some inputs, namely, to paraphrase some of the results of the translation which still sounded like Indonesian when read. There were still some problems in the use of passive sentences and some input in the design of the guidebook, which included the use of spaces and layout on the product guidebook. According to visitors, the guidebook provided complete and precise information, but there was some room for improvement, namely, to develop the design of the guidebook further to attract readers. The result of this research was that the bilingual guidebook about seven interesting and popular beaches. The purpose of this research was to develop the guidebook and help promote those beaches to the people. Besides that, the guidebook also gave detailed information about those seven beaches to local and foreign tourists who want to visit the beaches.